2020
DOI: 10.1111/pde.14265
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lipomas and macrocephaly as early signs of PTEN hamartoma tumor syndrome

Abstract: Superficial lipoma is a painless, soft subcutaneous mass that develops slowly and results from benign proliferation of mature adipocytes. 1 It accounts for approximately 5% of soft-tissue tumors in children. 2 Most are localized in the neck, trunk, or upper thighs. Lipomatosis, defined by an abnormal deposition of fat tissue or multiple lipomas, is rare in children and has been associated with Bannayan-Riley-Ruvalcaba syndrome or Cowden syndrome. 2,3 These two genetic syndromes are characterized by a phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Macrocephaly is a major sign in PHTS. All our patients presented macrocephaly, as it has been reported in several other cohorts [ 5 , 20 ]. Seventy-eight percent of our sample (7/9) had a head circumference SD score over + 4, greater than a French cohort and similar to an Italian cohort, which are the studies closest to the Spanish population [ 5 , 20 ].…”
Section: Discussionsupporting
confidence: 78%
“…Macrocephaly is a major sign in PHTS. All our patients presented macrocephaly, as it has been reported in several other cohorts [ 5 , 20 ]. Seventy-eight percent of our sample (7/9) had a head circumference SD score over + 4, greater than a French cohort and similar to an Italian cohort, which are the studies closest to the Spanish population [ 5 , 20 ].…”
Section: Discussionsupporting
confidence: 78%
“…As such, children often do not meet PHTS diagnostic criteria without a suggestive family history, which may delay their diagnosis. While penile macules may be one of the primary physical finding pointing to a diagnosis of BRRS, recent studies raise new criteria for consideration 2 . We offer the association of gingival hyperpigmentation and diffuse, facial, and ear angiofibromas as a potential expansion to the BRRS and pediatric PHTS clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…While penile macules may be one of the primary physical finding pointing to a diagnosis of BRRS, recent studies raise new criteria for consideration. 2 We offer the association of gingival hyperpigmentation and diffuse, facial, and ear angio-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology of penile macules from a patient with BRRS showed hyperplasia of the epidermis with increased pigment in the basal layer and slight increase in the number of melanocytes ( 47 ). In a case series of children with PTHS, genital lentiginosis was found in all patients with genital evaluation as early as age 2.5 years ( 58 ). A study of patients with PTEN mutations from 1 to 26 years found that penile macular pigmentation was present in 41% of males in the cohort, with earliest report of pigmentation occurring at 15 months of age ( 57 ).…”
Section: Mucocutaneous Manifestations Of Cowden Syndromementioning
confidence: 99%